Further analysis of coat protein gene sequences of Tobacco streak virus isolates from diverse locations and hosts in India - and R.K. JAIN*, SUDEEP BAG, R.S. SINGH (Indian Phytopathology, 2008)
Diversity in Tobacco streak virus (TSV) isolates was determined by analyzing both nucleotide and deduced amino acid sequences of coat protein (CP) gene of 21 isolates originating from 17 different hosts of six different families and five different locations of India. TSV isolates were uniform in CP length (717 nt and 238 aa) and shared high degree of sequence conservation both at nucleotide and amino acid levels (96- 100%), suggesting their common origin. However, three new TSV isolates in the present study originating from groundnut (GN-AP), chilli (CH-UP) and sunflower (SF-TN2) were divergent from the previously known isolates. Among these, GN-AP isolate was unique and did not cluster with rest of the isolates.